Interaction between the DNAH9 gene and early smoke exposure in bronchial hyperresponsiveness. Issue 4 (21st January 2016) - Dizier, Marie-Hélène; Nadif, Rachel; Margaritte-Jeannin, Patricia; Barton, Sheila J.; Sarnowski, Chloé; Gagné-Ouellet, Valérie; Brossard, Myriam; Lavielle, Nolwenn; Just, Jocelyne; Lathrop, Mark; Holloway, John W.; Laprise, Catherine; et al.
A previous genome-wide linkage scan of bronchial hyperresponsiveness (BHR) in the French Epidemiological study on the Genetics and Environment of Asthma (EGEA) families, performed in the presence of a gene×early-life environmental tobacco smoke (ETS) exposure interaction, showed the strongest interaction in the 17p11 region where linkage was detected only among unexposed siblings. Our goal was to conduct fine-scale mapping of 17p11 to identify single nucleotide polymorphisms (SNPs) interacting with ETS that influence BHR. Analyses were performed in 388 French EGEA asthmatic families, using a two-step strategy: 1) selection of SNPs displaying family-based association test (FBAT) association signals (p≤0.01) with BHR in unexposed siblings, and 2) a FBAT homogeneity test between exposed and unexposed siblings plus a robust log-linear interaction test. A single SNP reached the threshold (p≤3×10 −3 ) for significant interaction with ETS using both interaction tests, after accounting for multiple testing. Results were replicated in 253 French-Canadian families, but not in 341 UK families, probably due in part to differences in phenotypic features between datasets. The SNP showing significant interaction with ETS belongs to DNAH9 (dynein, axonemal, heavy chain 9), a promising candidate gene involved in respiratory cilia mobility and associated with primary ciliary dyskinesia, a disease associated with abnormalities of pulmonary function. An interaction between the DNAH9 gene and early smoke exposure in bronchial hyperresponsiveness was found http://ow.ly/V9qft